Laboratory Calibration of the Spectrum Field Scout TDR 300 - W. Dyer; D. Bremer; P. Rossini; M. Stone; A. Patrignani (Kansas Agricultural Experiment Station Research Reports, 2021)
Soil moisture sensors (SMSs) are a useful tool that aid in data-driven water management decisions. However, default factory calibrations can be inaccurate and soil-specific calibrations are often required to obtain higher accuracy in the determination of soil water storage and plant available water. In this study, we conducted a lab calibration for the Field Scout TDR 300, which is a popular SMS used in the turfgrass industry. Five soils of different soil textural classes were packed in containers with known soil moisture for the laboratory calibration. The logarithmic model best fit the data for the course- and fine-textured soils, with a root mean square error (RMSE) value of 0.027 and 0.035 cm3cm-3, respectively. These two calibration curves help to estimate volumetric water content more accurately for native and sand-based soils.
Keywords: soil moisture sensor; soil water; calibration